Ecological renovation process of Nanjing's housing stock built between 1840 and 1949, China. Issue 3 (3rd May 2020) - Wu, Jinxiu; Dong, Wei; Li, Yonghui; Fu, Xiuzhang
ABSTRACT: Numerous in number and mostly still in use, buildings built between 1840 and 1949 are valuable assets in the rapid development and renovation of Chinese cities. However, due to lack of maintenance and being inhabited mainly by the elderly and people with low incomes, many of these buildings are in poor condition and have much higher possibilities of being demolished. The objectives of ecological renovation presented in this paper are to improve building performance and to achieve higher levels of comfort and lower levels of energy consumption. The housings in Zhong-nong-li block in Nanjing are used as an example in this paper to show how a strategy of "basic" renovation and "thorough" renovation is used in the ecological renovation of housing stock between 1840 and 1949 in China. The paper demonstrates that these are very practical steps for this building stock in China and could not only help to balance social and economic factors in practice, but also improve the living conditions of the residents, and endow the old houses with a new, long life. Numerical simulations of the natural day lighting and ventilation situations before and after renovation are made to show the improvement in building performance after renovation.